Development of a simple and valid method for the trace determination of phthalate esters in human plasma using dispersive liquid–liquid microextraction coupled with gas chromatography–mass spectrometry. Issue 22 (10th October 2017) - Ebrahim, Karim; Poursafa, Parinaz; Amin, Mohammad Mehdi
Abstract: A new method was developed for the trace determination of phthalic acid esters in plasma using dispersive liquid–liquid microextraction and gas chromatography with mass spectrometry analysis. Plasma proteins were efficiently precipitated by trichloroacetic acid and then a mixture of chlorobenzene (as extraction solvent) and acetonitrile (as dispersive solvent) rapidly injected to clear supernatant using a syringe. After centrifuging, chlorobenzene sedimented at the bottom of the test tube. 1 μL of this sedimented phase was injected into the gas chromatograph for phthalic acid esters analysis. Different factors affecting the extraction performance, such as the type of extraction and dispersive solvent, their volume, extraction time, and the effects of salt addition were investigated and optimized. Under the optimum conditions, the enrichment factors and extraction recoveries were satisfactory and ranged between 820–1020 and 91–97%, respectively. The linear range was wide (50–1000 ng/mL) and limit of detection was very low (1.5–2.5 ng/mL for all analytes). The relative standard deviations for analysis of 1 μg/mL of the analytes were between 3.2–6.1%. Salt addition showed no significant effect on extraction recovery. Finally, the proposed method was successfully utilized for the extraction and determination of the phthalic acid esters in human plasma samples and satisfactory results were obtained.